2022
DOI: 10.3390/colloids6020031
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Flows and Interfacial Shape Modulation Controlled by the Thermal Action of Light Energy

Abstract: The review covers the research on thermocapillary convection caused by the thermal action of laser radiation in single-layer and bilayer liquid systems of capillary thickness. The advantages of using optical radiation are the instantaneous delivery of thermal energy to a place on demand (a bulk phase, interfaces); low radiation power required; concentrating heat flux on a spot of a few micrometers; the production of arbitrary spatial distributions of radiation intensity; and, as a result, corresponding thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…As a result, the liquid layer near the heater thins until the onset of particle transport by the bottom current, which occurs when the temperature gradient satisfies the condition of eq . Experiments , have shown that, at a fixed temperature difference or heat source power, the depth of the thermocapillary cavity, Δ h , in the center increases with decreasing the initial thickness of layer. Thus, in a thin layer, the cavity depth will be significant.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the liquid layer near the heater thins until the onset of particle transport by the bottom current, which occurs when the temperature gradient satisfies the condition of eq . Experiments , have shown that, at a fixed temperature difference or heat source power, the depth of the thermocapillary cavity, Δ h , in the center increases with decreasing the initial thickness of layer. Thus, in a thin layer, the cavity depth will be significant.…”
Section: Resultsmentioning
confidence: 99%
“…The fluid then flew outward along the interface from the high-temperature region with respect to the laser-acted zone to the low-temperature region. An inward flow inside the droplet arose from the colder region due to mass conservation, forming a complete circulation loop. Actually, this circular flow could be stable in the case of low laser power (38 mW), which was characterized by adding polystyrene (PS) tracer microspheres into the droplet to probe Marangoni convection. There was a stable Marangoni flow and no deformation of droplet interface (Movie S2).…”
mentioning
confidence: 99%